Association of burnout and working environment conditions in respiratory care professionals in Saudi Arabia: a cross-sectional study - Saad Al-Anazi; Saad Al-Anazi; Syed Shahid Habib; Thamir Al-khlaiwi; Abdulaziz Alhomaidi Alodhayani; Abdulmueen Alotaibi; Abdulmueen Alotaibi; Saja Aldulejan; Sufana Al Safadi; Fahad Saad Alshammari; Aqeelah Marar; Afaf Alrashdi; et al. (Frontiers in Public Health)
IntroductionBurnout is a pervasive issue in healthcare, and it impacts both the wellbeing of healthcare professionals and the quality of patient care. This study examines factors associated with burnout and working environment among respiratory therapists in Saudi Arabia.MethodsA structured questionnaire was used to collect data from respiratory therapists. We collected 315 questionnaires including burnout assessment. Multinomial logistic regression was used to assess the relationship between various variables and the likelihood of experiencing severe burnout and personal achievement problems.ResultsMarital status was a significant predictor of severe burnout (p = 0.001), with single individuals having 8.2 times higher odds than married individuals. Working longer than 44 h per week was associated with a 19.3-fold increase in the odds of severe personal achievement issues compared to those working 40–44 h per week (p < 0.001). Age, gender, living arrangements, education, employment status, and salary level were not significant predictors of severe burnout or personal achievement issues.Conclusion with discussionThe findings highlight that marital status and extended working hours are significantly associated with increased burnout among respiratory therapists in Saudi Arabia. These results underscore the importance of social support networks and work-life balance in mitigating burnout risks within this profession.